Pengaruh Iklim Kelas, Kecerdasan Adversitas, Dan Dukungan Orang Tua Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Ekonomi Di SMA Batik 2 Surakarta - Iffah Qodriyana; Mintasih Indriayu; Dewi Kusuma Wardani (Journal on Education, 2024)
The purpose of this research is to determine the influence of class climate, adversity intelligence, and parental support on student learning motivation in economics subjects at SMA Batik 2 Surakarta. The research method used was quantitative with a population of SMA Batik 2 Surakarta students. The sampling technique used simple random sampling with a sample of 250. Data collection used documentation and questionnaires, and data analysis used multiple linear analysis. The results of this research show (1) there is an influence of classroom climate on students' learning motivation in economics subjects at SMA Batik 2 Surakarta with a calculated t value > t table (4.529 > 1.968) and a significance of 0.000 < 0.05. (2) there is an influence of adversity intelligence on students' learning motivation in economics subjects at SMA Batik 2 Surakarta with a calculated t value > t table (6.889 > 1.968) and a significance of 0.000 < 0.05. (3) there is an influence of parental support on students' learning motivation in economics subjects at SMA Batik 2 Surakarta with a calculated t value > t table (3.921 > 1.968) and a significance of 0.000 < 0.05. (4) there is an influence of class climate, adversity intelligence, and parental support on students' learning motivation in economics subjects at SMA Batik 2 Surakarta based on the calculated F value > F table (98.210 > 1.968) and a significance of 0.000 < 0.05.